THE HERBACEOUS DICOTYLEDONOUS AXIS FROM THE DECCAN INTERTRAPPEAN BEDS OF MOHGAONKALAN - PRATIBHA F. DHABARDE,; M. T. SHEIKH,; P. D. KOLHE, (The Bioscan, 2011)
The present axis appears pentangular, herbaceous, dicotyledonous showing secondary growth of diffuse porous type. It consist of bark, cork, secondary cortex, secondary phloem, secondary xylem, primary xylem and pith. cortex parenchymatous, secondary xylem consists of vessels, rays, parenchyma, and fibres. Vessel mostly solitary, rays uniseriate and homogenous paratracheal vesicentric parenchyma, primary xylem endarch. Pith large with mucilage cells.